Estrategia de servicios web abiertos para el desarrollo de la sociedad del conocimiento - Pérez Castillo, José Nelson; Castro Vargas, Blanca Magdalena (Ingeniería, 2001)
This paper defines the open source Web services characteristics that based on international standards would have to follow to solve the core areas of the knowledge society: business services, educational services and government services. It would have to allow produce in a sustainable way the main products and services of a post modern society.